2020
DOI: 10.3390/molecules25143280
|View full text |Cite
|
Sign up to set email alerts
|

Role of Phase Change Materials Containing Carbonized Rice husks on the Roof-Surface and Indoor Temperatures for Cool Roof System Application

Abstract: This study researches the effect of phase change materials (PCMs) containing carbonized rice husks (CRHs) in wood plastic composites (WPCs) as roof finishing materials on roof-surface and indoor temperatures. A cool roof miniature model was prepared, and measurements were taken using three fixed temperatures of 30 to 32 °C, 35 to 37 °C, and 40 to 42 °C. Sodium sulfate decahydrate (Na2SO4·10H2O) and paraffin wax were selected as the PCMs. CRHs were used as additives to improve the thermal conductivities of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…They determined that a 2° inclination angle for the PCM layer yielded optimal results, with reductions in ceiling temperature of up to 2.38°C and daily heat gain reduced by up to 16% compared to non-PCM rooms. Kim et al [42] used PCMs with carbonised rice husks to lower roof surface and interior temperatures. Compared to roofs without PCMs, the combination reduced surface temperature to 74.6°C, with a maximum difference of 11°C.…”
Section: Microencapsulated Pcms Have Been Widely Studied For Their Po...mentioning
confidence: 99%
“…They determined that a 2° inclination angle for the PCM layer yielded optimal results, with reductions in ceiling temperature of up to 2.38°C and daily heat gain reduced by up to 16% compared to non-PCM rooms. Kim et al [42] used PCMs with carbonised rice husks to lower roof surface and interior temperatures. Compared to roofs without PCMs, the combination reduced surface temperature to 74.6°C, with a maximum difference of 11°C.…”
Section: Microencapsulated Pcms Have Been Widely Studied For Their Po...mentioning
confidence: 99%
“…In addition, various studies natural heat convection has being conducted in both theoretical and application regards, including modified turbulent modeling, computational fluid dynamics (CFD) and simulation, nanomaterial additives for thermal-physical improvement and practical engineering optimization, over recent years [18,19]. Shanmuganathan et al [20] experimented on building energy efficiency coupled with reflective coating under natural heat convection boundary conditions.…”
Section: Introductionmentioning
confidence: 99%
“…25 It is one of the most mass-produced fatty acids. 25 Thermal energy storage materials (TESMs) with a melting point of 40−45 °C are specifically suitable for the following applications: (1) thermal management (passive cooling) for roofs and walls in areas with summer daytime temperature often over 30 °C (it has been found that the application of TESMs (with a melting point in the range of 40−45 °C) for roof thermal management is significantly (e.g., 1.5−4°C 26 ) more effective on lowering the indoor temperature than the ones with a melting point in the range of 25−30 °C), (2) thermal management of a heat exchanger for greenhouse heating applications, 27 (3) thermal management (heat recovery) of a heat pump, 28 and (4) body and water warmer. 29 Therefore, lauric acid is the target PCM material in this study for creating size-tunable polymer-shelled lauric acid nanocapsules.…”
Section: ■ Introductionmentioning
confidence: 99%